Literature Review Benefits of Moxa Therapy for Postpartum Women - Yulizawati, Yulizawati; Putri, Viorika Marsafa (Journal of Midwifery, 2024)
Background: The postpartum period is a crucial period for the mother's recovery after childbirth. One of the health problems that commonly occurs in postpartum mothers is low back pain (LBP), which can affect the quality of life and ability to care for the baby. Moxa therapy is a traditional treatment method that is believed to reduce pain and speed up recovery. Objective: This article aims to review the benefits of moxa therapy for postpartum women Method: A literature search was carried out through the PubMed, Google Scholar, and Scopus databases using the keywords Moxa therapy postpartum, moxibustion for postpartum recovery, moxa massage for postpartum mothers, and traditional Chinese medicine for postpartum. Articles that met the inclusion criteria were published within the last 5 years and discussed the benefits of moxa therapy for postpartum women. Conclusion: Moxa therapy has various benefits in reducing lower back pain in postpartum women, including improving blood circulation, reducing inflammation, relaxing tense muscles, and improving quality of life. With increasing interest in traditional medicine, moxa therapy may be an effective and safe option for postpartum women with lower back pain.